2002
DOI: 10.1046/j.1523-5378.2002.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Cyclooxygenase‐2 Inhibitor and Non‐Selective NSAIDs on Helicobacter pylori‐Induced Gastritis in Mongolian Gerbils

Abstract: Our animal study showed that H. pylori infection induced COX-2 expression and increased prostaglandin concentration. Administration of NSAIDs decreased the prostaglandin concentration, but did not increase mucosal damage in H. pylori-induced gastritis. Selective COX-2 inhibitors, instead of conventional NSAIDs, had no beneficial effect on preventing mucosal damage in H. pylori-induced gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…At 2 or 4 or 8 wks after the bacterial inoculation, gerbils were sacrificed, and gastric mucosal samples were taken for biopsy rapid urease test, microbial culture and histology. H. pylori status was defined as positive if all the three methods gave positive results . A negative H. pylori status was considered if all tests gave concordant negative results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 2 or 4 or 8 wks after the bacterial inoculation, gerbils were sacrificed, and gastric mucosal samples were taken for biopsy rapid urease test, microbial culture and histology. H. pylori status was defined as positive if all the three methods gave positive results . A negative H. pylori status was considered if all tests gave concordant negative results.…”
Section: Methodsmentioning
confidence: 99%
“…H. pylori status was defined as positive if all the three methods gave positive results. 26,27 A negative H. pylori status was considered if all tests gave concordant negative results. The remaining stomach samples were collected for immunofluorescence analysis, which was performed on paraffin-embedded gastric tissues by using antibodies against pSTAT3 Tyr705 (1:50), STAT3 (1:200) and TMEFF2 (1:200).…”
Section: Chromatin Immunoprecipitation and Real-time Pcr Quantificatimentioning
confidence: 99%
“…However, a few studies failed to confirm the synergistic interaction between NSAIDs and H. pylori infection [35][36][37][38]. Kim [36,37]. In a clinical study conducted by Scheiman et al, rofecoxib, a COX-2 inhibitor, did not significantly affect gastritis scores in patients with H. pylori infection [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that genetic deficiency of the COX-1 or COX-2 isoform exacerbated the severity of H. pylori-induced gastritis [23], suggesting that inhibition of COX activity is at least part of the mechanism that NSAIDs exhibit the enhancing effects. However, a few studies failed to confirm the synergistic interaction between NSAIDs and H. pylori infection [35][36][37][38]. Kim et al reported that indomethacin and NS-398 decreased gastric inflammation induced by H. pylori infection in mice [35], while Bhang et al and Magari et al reported that administration of selective COX-2 inhibitors, NS-398, and etodolac did not increase mucosal damage in H. pylori-induced gastritis [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation